2004
DOI: 10.1007/s00213-004-1980-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose on tobacco craving. Is it mediated by tryptophan and serotonin?

Abstract: Glucose attenuates tobacco craving and withdrawal symptoms in temporarily abstinent smokers. This is accompanied by a decrease in plasma TRP and a sex dependent increase in blood serotonin. Further studies assessing the direct effect of glucose on brain serotonin are needed to ascertain whether a glucose induced reduction in craving is associated with an increase in brain serotonin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…However, among smokers also using an approved smoking cessation medicine (nicotine replacement or bupropion), glucose tablets increased their 6-month quit rate (18.2% vs 12.6%, p<0.05). The inconsistent but promising results of glucose tablets for smoking cessation in clinical trials mirrors the inconsistent but sometimes promising results of laboratory studies of the effects of glucose on cigarette craving (e.g., West and Willis 1998;West et al 1999;Harakas and Foulds 2002;Berlin et al 2005). Given that glucose could be an extremely costeffective smoking cessation aid, we agree with West et al that it is worthy of further examination.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…However, among smokers also using an approved smoking cessation medicine (nicotine replacement or bupropion), glucose tablets increased their 6-month quit rate (18.2% vs 12.6%, p<0.05). The inconsistent but promising results of glucose tablets for smoking cessation in clinical trials mirrors the inconsistent but sometimes promising results of laboratory studies of the effects of glucose on cigarette craving (e.g., West and Willis 1998;West et al 1999;Harakas and Foulds 2002;Berlin et al 2005). Given that glucose could be an extremely costeffective smoking cessation aid, we agree with West et al that it is worthy of further examination.…”
supporting
confidence: 65%
“…Most published studies, and particularly those examining behavioral effects, involve diabetics or healthy subjects given a single large dose of oral glucose (e.g., 25-75 g; e.g., Sunram-Lea et al 2001;Berlin et al 2005). In the trials reported by West et al, participants typically consumed four to 15 3-g tablets per day (12-45 g per day), and in their earlier experimental study, West et al (1999) found that a "single dose" of four 3-g glucose tablets (i.e., 12 g) reduced craving for a cigarette.…”
mentioning
confidence: 99%
“…Two exploratory studies were performed at Singapore's National University Hospital (NUH). The first (Experiment 1) was a pilot study to investigate the efficacy of TEAS as a method for relieving acute cravings in a controlled situation, where smokers were not allowed to smoke [25]. This experiment was initiated in March 2005 to assess the feasibility, the acceptability by the subjects and the dropout rate.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study by Helmers and Young (1998) had found that sucrose reduced withdrawal discomfort but could not test for an effect on craving because of chance differences in this measure at baseline. More recently, Berlin et al (2005) found that a glucose drink significantly reduced craving for cigarettes in abstaining smokers compared with a sweet tasting control, and that this was mediated by an increase in tryptophan uptake into the central nervous system. Tryptophan is a serotonin precursor, and this would be expected to raise brain serotonin levels in a manner that might reduce "physiological hunger" (West 2001).…”
mentioning
confidence: 99%